Effects of animal protein supplementation of mothers, preterm infants, and term infants on growth outcomes in childhood: a systematic review and meta-analysis of randomized trials. Issue 2 (8th June 2019) - Pimpin, Laura; Kranz, Sarah; Liu, Enju; Shulkin, Masha; Karageorgou, Dimitra; Miller, Victoria; Fawzi, Wafaie; Duggan, Christopher; Webb, Patrick; Mozaffarian, Dariush
ABSTRACT: Background: Child stunting is a major public health problem, afflicting 155 million people worldwide. Lack of animal-source protein has been identified as a risk, but effects of animal protein supplementation are not well established. Objective: The aim of this study was to investigate effects of animal protein supplementation in mothers, preterm infants, and term infants/children on birth and growth outcomes. Methods: PubMed, EMBASE, Cochrane library, Web of Science, Cumulative Index of Nursing and Allied Health Literature, and Latin American and Caribbean Health Sciences Literature were searched for randomized controlled trials of animal protein supplementation in mothers or infants and children (≤age 5 y), evaluating measures of anthropometry (≤age 18 y). Main outcomes included birth weight, low birth weight, small for gestational age at birth; height, height-for-age, weight, weight-for-age, weight-for-length, stunting, and wasting ≤18 y of age. Data were extracted independently in duplicate, and findings pooled using inverse variance meta-analysis. Heterogeneity was explored using I 2, stratified analysis, and meta-regression, and publication bias by funnel plots, Egger's test, and fill/trim methods. Results: Of 6808 unique abstracts and 357 full-text articles, 62 trials were included. The 62 trials comprised over 30, 000 participants across 5 continents, including formula-based supplementation in infants and food-based supplementation in pregnancy and childhood. Maternal supplementation increased birth weight by 0.06 kg, and both formula and food-based supplementation in term infants/young children increased weight by ≤0.14 kg. Neither formula nor food-based supplementation for term infants/young children increased height, whereas the height-for-age z -score was increased in the food-based (+0.06 z -score) but not formula-based (−0.11 z -score) trials reporting this outcome. In term infants, the weight-for-length z -score was increased in trials of formula (+0.24 z -score) and food supplementation (+0.06 z -score), whereas food supplementation was also associated with reduced odds of stunting (−13%). Conclusions: Supplementation of protein from animal-source foods generally increased weight and weight-for-length in children, but with more limited effects on other growth outcomes such as attained height.